The Traumatizing Politics of Transitional Justice Policies: The Macedonian Case of Lustration - Trajkovski, Ilo (Macedonian Sociological Association, 2008)
This contribution analyzes the political aspects of the ways in which the Republic of Macedonia deals with some traumatic fragments of its history. The main object of analysis are the measures (policies) undertaken by the state aimed at dealing with the effects of traumatic experiences of Macedonian citizens from the communist persecutions (during the communist period and immediately after the independence). The analysis argues that, by politicizing certain limited traumatic experiences, the political circles traumatize transitional justice policies. They transpose individual and generational traumatic experiences into collective and memorable trauma. Thus, instead of a politics of truth and forgiveness (without forgetting) in the name of building a common future, transitional justice works as a politics of retaliation, i.e. as politics of fear, of a possible unforeseen future of approved and unpunished violence. Theoretically, this interpretation of the Macedonian transitional justice relies on the political-sociological concept of trauma. According to this concept, for understanding the trauma and especially the traumatic syndrome, the trust in the institutions of power is of crucial importance, and in this case, in the institutions of political power of the Republic of Macedonia. Seen from this perspective, the policies for dealing with traumatic experiences and the subsequent transitional justice appear mainly as issues of the political unity in the Republic of Macedonia.
Keywords: collective trauma, politics of trauma, transitional justice, truth establishment, Macedonian lustration